Probability models for assessing transport terminal operation - Baublys, Adolfas (Transport, 2007)
The paper considers the following problems: 1) The development of a probability model to determine malfunction of the terminal; 2) Determining the emergency situations at the terminal based on statistical data; 3) Optimizing the effect of failures on the operation of the terminal; 4) Identifying the conflicting situations in making managerial decisions at the terminal.First Published Online: 27 Oct 2010